The Interplay Between Organisational Learning Culture, The Manager as Coach, Self-Efficacy and Workload on Employee Work Engagement - Ladyshewsky, Rick; Taplin, Ross (Oxford Brookes University, 2018)
A cross sectional convenience sample of 195 MBA students answered questions which explored the impacts of managerial coaching on work engagement. Measures of organisational learning culture (OLC), self-efficacy, manager quality and workload were considered as potential influences on work engagement. Analysis was carried out using structural equation modelling. Results indicate that the positive influence of managerial coaching on employee work engagement is mediated by OLC. Self-efficacy and workload also influence work engagement in a positive manner independently. Organisations that invest in the development of coaching skills of managers can enhance the OLC and thereby the work engagement of employees.